The New Algorithms Of Machine Learning For Education People With Special Needs; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Khaperskaya A. V. Alena Vasilievna (2018, 2018)
Title screen